The Concept of Differentiated Learning in the Qur'an: The Perspective of Ibn Kathir's Interpretation - Muhammad Maulana Ibrahim; Syamsu Nahar; Yusnaili Budianti (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2025)
The purpose of this study is to describe the concept of differentiated learning in the Qur'an based on Ibn Kathir's interpretation. The research method used is qualitative with a thematic interpretation approach. Data were collected through literature studies from the book Tafsir Ibn Kathir, Islamic education literature, and academic references related to the concept of differentiated learning. The results of the study show that, according to Ibn Kathir, these three verses together emphasize that ideal education is education that respects differences, understands individual character, and teaches the truth gently and wisely. The concept of differentiated learning from the perspective of Ibn Kathir's interpretation is based on the principle that every human being possesses unique potential that demands a varied learning approach. Consequently, the Qur'anic values ​​explained by Ibn Kathir are highly relevant to the needs of modern education, confirming that the concept of differentiated learning is not new in Islam but is deeply embedded in the teachings of the Qur'an.